Morphometric affinities and direct radiocarbon dating of the Toca dos Coqueiros’ skull (Serra da Capivara, Brazil) - Menendez, Lumila Paula (2022)
The biological variation of the earliest skeletons of South America has been intensely debated for the last two centuries. One of the major research constraints has been the limited number of available samples dating to the early Holocene. We here present the first direct radiocarbon-date for the early Holocene human skeleton from Toca dos Coqueiros (Serra da Capivara, Brazil), also known as “Zuzu” (8640 ± 30 BP; 9526–9681 cal years BP). We performed craniometric analyses using exclusively samples from Brazil, to revisit the sex of the skeleton, and to discuss the evolutionary processes involved in the occupation of the continent. The sex of the individual was estimated as a female when compared to late and early Holocene individuals, but as a male when compared only to the early Holocene series. We also found that Zuzu presents the strongest differences with the late Holocene Guajajara individuals, located nearby, and the strongest similarities with the early Holocene series from Lagoa Santa, attesting for solid biological affinities among early Holocene individuals from Brazil, as well as a moderate level of morphological variation among them. This suggests that the early individuals were part of the same heterogeneous lineage, possibly a different one from which late Holocene populations diverged.